The Effect of Concentration of Pectin and Carrageenan on The Quality of Ginger Jelly Candy - Wirda Juwita P; Herla Rusmarilin; Era Yusraini (Universitas Sumatera Utara, 2014)
The research was conducted to find the effect of concentration of pectin and carrageenan on the quality of ginger jelly candy. This research was using completely randomized design with two factors i.e.: concentration of pectin (P): 0.8%, 0.9%, 1.0%, 1.1% and concentration of carrageenan (K): 2%, 3%, 4%. The parameters analyzed were moisture content, total acid, total soluble solid, crude fiber content, ash content, scores of colour and texture, and hedonic colour, taste, and texture. The results showed that the concentration of pectin had highly significant effect on moisture content, total acid, total soluble solid, crude fiber content, ash content, scores of colour and texture, and hedonic colour, taste, and texture. The concentration of carrageenan had highly significant effect on moisture content, total acid, total soluble solid, crude fiber content, ash content, scores of colour and texture, and hedonic taste and texture, and had significant effect on the hedonic colour. The interaction between concentration pectin and carrageenan had highly significant effect on score of texture and hedonic taste, and had significant effect on moisture content, crude fiber content, and score of colour. The best concentration of pectin and carrageenan had been viewed through the hedonic of the product. The concentration of pectin of 1.0% and carrageenan of 3% had a better outcome on the quality of ginger jelly candy. Key words: Concentration of carrageenan, concentration of pectin, ginger jelly candy